2006
DOI: 10.1115/1.2427071
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Metal-Oxide Nanofluids: Particle Size Dependence and Effect of Laser Irradiation

Abstract: The thermal conductivity of water- and ethylene glycol-based nanofluids containing alumina, zinc-oxide, and titanium-dioxide nanoparticles is measured using the transient hot-wire method. Measurements are performed by varying the particle size and volume fraction, providing a set of consistent experimental data over a wide range of colloidal conditions. Emphasis is placed on the effect of the suspended particle size on the effective thermal conductivity. Also, the effect of laser-pulse irradiation, i.e., the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
118
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(129 citation statements)
references
References 18 publications
7
118
0
4
Order By: Relevance
“…The decrease in thermal conductivity with increasing nanoparticle size was also noted when studying other nanofluids [9][10][11][12]. In [13] it was asserted that the thermal conductivity coefficient increases linearly with decreasing particle size (the measurements were carried out in water-based nanofluid with nanoparticles of TiO2 and ZnO).…”
Section: Introductionmentioning
confidence: 96%
“…The decrease in thermal conductivity with increasing nanoparticle size was also noted when studying other nanofluids [9][10][11][12]. In [13] it was asserted that the thermal conductivity coefficient increases linearly with decreasing particle size (the measurements were carried out in water-based nanofluid with nanoparticles of TiO2 and ZnO).…”
Section: Introductionmentioning
confidence: 96%
“…E-mail: seshim@inha.ac.kr conductivity of water and ethylene glycol containing boron nitride (BN), zinc oxide (ZnO), and titanium dioxide. 7 Kou et al explored the effect of the particle size of BN on the thermal conductivity of silicone rubber. The thermal conductivity of the prepared composites was improved with BN particles with a smaller diameter at the same volume fraction.…”
Section: Introductionmentioning
confidence: 99%
“…At low concentrations, the slope was greater than at high concentrations. Most thermal conductivity data in the literature for Al 2 O 3 -water nanofluids showed that with increasing nanoparticle volume concentration, the thermal conductivity also increased [21][22][23][24][25][26][27][28][29][30], however, the intensity of the increase decreased for the larger volume concentrations.…”
Section: Effect Of Volume Concentrationmentioning
confidence: 99%